Exploring context for implementation of inclusive education for children with developmental disabilities in mainstream primary schools in Ethiopia. - Elisa Genovesi; Ikram Ahmed; Moges Ayele; Winini Belay; Olivia Burningham; Amanda Chen; Fikirte Girma; Liya Tesfaye Lakew; Charlotte Hanlon; Rosa Anna Hoekstra (PLoS ONE)
A large gap in provision of services for children with developmental disabilities (DD) has been identified in Ethiopia, especially in the education system. Including children with disabilities in mainstream schools is encouraged by policies, but progress in this direction has been limited. This study aimed to explore stakeholders' perspectives on contextual factors relevant for inclusive education for children with DD in mainstream schools in Ethiopia, with a focus on Adis Ababa. Data were collected through semi-structured interviews with 39 local stakeholders, comprising caregivers of children with DD, school teachers and principals/managers, non-governmental organisation representatives, government officials, clinicians and academics/consultants. We used template analysis to code the data and map them onto domains of the Context and Setting dimensions of the Context and Implementation of Complex Interventions framework. Stakeholders discussed frameworks in the Legal and Ethical context endorsing the right of all children to education. However, they reported multiple reasons why children with DD in Ethiopia have limited access to education, either in special or mainstream schools. First, individual features, such as gender and support needs, discussed in the Epidemiological context, may affect the likelihood of a child with DD to be accepted in school. Transportation challenges are a key barrier in the Geographical context. Socio-economic and Socio-cultural contexts present barriers at the levels of the nation, school and family, mostly related to limited services and material and financial resources and limited awareness of DD. Stakeholders believe the currently limited but growing commitment in the Political context can support progress towards the removal of these barriers. Our findings can form the basis for development of an implementation plan that addresses such barriers and capitalises on existing facilitators.